2018
DOI: 10.1093/ajcn/nqy099
|View full text |Cite|
|
Sign up to set email alerts
|

Serum untargeted metabolomic profile of the Dietary Approaches to Stop Hypertension (DASH) dietary pattern

Abstract: An untargeted metabolomic platform identified a broad array of serum metabolites that differed between the DASH diet and 2 other dietary patterns. This newly identified metabolite panel may be used to assess adherence to the DASH dietary pattern. This trial was registered at http://www.clinicaltrials.gov as NCT03403166.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 51 publications
8
102
0
Order By: Relevance
“…Moreover, hippurate was associated with lower risk of all-cause mortality, even when adjusting for traditional risk factors. N-methylproline was recently shown to associate with healthy eating, to be decreased after following the Dietary Approaches to Stop Hypertension (DASH) diet [23] and to associate with decreased risk of CAD and all-cause mortality in individuals free from CMD [24]. In concert with these previous findings, our study indicates that healthy eating, particularly intake of citrus fruit, is beneficial in individuals with diabetes.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, hippurate was associated with lower risk of all-cause mortality, even when adjusting for traditional risk factors. N-methylproline was recently shown to associate with healthy eating, to be decreased after following the Dietary Approaches to Stop Hypertension (DASH) diet [23] and to associate with decreased risk of CAD and all-cause mortality in individuals free from CMD [24]. In concert with these previous findings, our study indicates that healthy eating, particularly intake of citrus fruit, is beneficial in individuals with diabetes.…”
Section: Discussionsupporting
confidence: 78%
“…A large number of metabolites in the human circulation derive directly from the digestion and metabolism of food components and constitute the food metabolome 5. Both endogenous plasma metabolites and metabolites from the food metabolome have been shown to correlate with certain dietary patterns estimated using questionnaires on dietary intake in cohort studies,6 and with certain food items in randomised controlled feeding trials 7. The connection between diet and the metabolome is particularly interesting because circulating levels of specific metabolites have previously been shown to predict future risk of type 2 diabetes,8 CAD9 and premature mortality 10.…”
Section: Introductionmentioning
confidence: 99%
“…A subgroup of eight participants underwent the fourth intervention with white beans, which was scheduled later. The subjects were on average 28 ± 6 years old (range: [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and had a BMI of 23.8 ± 3.6 kg m −2 (range: 18.6-28.9).…”
Section: Methodsmentioning
confidence: 99%
“…However, the complete clearance of its metabolism could not be estimated since this metabolite was still detected during the 24-48 h period, when the last sample was collected. It has been correlated with nut intake in different cross-sectional studies, [28][29][30][31] and it has also been associated with the Mediterranean diet [32] and the Dietary Approaches to Stop Hypertension [33] dietary patterns. Additionally, a study focused on peanut consumption also reported its presence in the breast milk of lactating women.…”
Section: Bfi For Legumesmentioning
confidence: 99%